Civic Participation and Citizenship in Turkey: A Comparative Study of Five Cities. Issue 3 (3rd July 2017) - Rumelili, Bahar; Çakmaklı, Didem
Abstract: This study explores whether and how participation in civil society organisations (CSOs) has transformed citizenship attitudes in different cities in Turkey, and how civic participation and citizenship attitudes are affected by local politico-cultural dynamics. The analysis is based on interviews conducted with representatives of 36 CSOs in five Turkish cities: Konya, Edirne, Diyarbakir, Trabzon, and Izmir. Our comparative analysis of the five cities reveals that civic life is more active in cities marked by high levels of religiosity (Konya) and politicised by conflict (Diyarbakir). On the other hand, politicisation of civic life through party dominance and clientelism, as in Edirne and Trabzon, undermines trust and discourages participation.